Massive nitrogen supersaturation to CoCrMo alloys for surface microstructure control - Tatsuhiko Aizawa; Tatsuya Funazuka; Tomomi Shiratori; Yohei Suzuki (Academia Materials Science)
CoCrMo alloys were plasma nitrided at 673 K for 14.4 ks to form a homogeneous nitrided layer with a thickness of 12 μm. This nitrogen-supersaturated layer had an expanded γ-phase with fine CrN precipitates. The nitrogen solute distributed homogeneously with its average content of 5 mass% toward the nitriding front end. This nitrided CoCrMo alloy matrix with its average grain size of 20 μm was plastically strained by the nitrogen supersaturation to significantly modify its original crystallographic microstructure. This nitrided layer consists of intensely textured grains with the orientation of (111) in the normal direction. The nitrided and textured layer had higher hardness 1,620 HV1N than the original polycrystalline CoCrMo matrix, 400 HV1N. Its average friction coefficient against the SUJ2 ball in dry was 0.4–0.5 under the applied load of 5 N and the sliding speed of 0.1 m/s.